Performance of double cropping silage maize with plastic mulch in the North China Plain. (25th July 2020) - Liang, Shuoshuo; Zhang, Xiying; Lu, Yang; An, Ping; Yan, Zongzheng; Chen, Suying
Abstract: North China Plain farmers often use maize ( Zea mays L.) silage for dairy cows. Double cropping of maize may be a feasible way to reduce annual water use and land required to produce feed. The objective of this study was to evaluate the possibility of growing a double crop of silage maize with and without plastic film mulch. An experiment was conducted between 2015 and 2018 and contained three treatments: double‐cropped (maize) plastic film mulch (2 M+PM), double‐cropped (maize) without plastic film mulch (2 M), and double‐cropped winter wheat ( Triticum aestivum L.) and summer maize (WW+SM). Net income, yield, water use efficiency (WUE), and annual water use were determined. The results indicated that silage dry matter yield and WUE were improved by 45.6 and 31.5%, respectively, using plastic film mulch compared with no mulch. Total water footprint in producing the silage was also reduced by 24% using plastic film mulch. The annual water use was reduced by 150–190 mm with 2 M+PM or 2 M compared with WW+SM. Average net income was 429, 926, and 1, 008 ha −1 in 2 M, 2 M+PM, and WW+SM, respectively. The results indicated that the advantages of the double‐silage maize system lie in the reduction in the amount of land required to produce maize silage for dairy cows. However, due to the limited growth duration for the double maize, high silage water contents reduced silage quality.